PENDAMPINGAN PENGOLAHAN DAGING AYAM BERBASIS REMPAH LOKAL UNTUK OPTIMALISASI PRODUKTIVITAS USAHA TERNAK UNGGAS DI DESA SALAMREJO, BLITAR - David Kurniawan; Nur Agustin Mardiana; Anang Widigdyo; Rosidi Azis (Jurnal Padamu Negeri, 2026)
This Community Service Program (PkM) focuses on solving the problems of low added value and market dependence among small-scale chicken farmers in Salamrejo Village, Blitar. Using a participatory action research and asset-based community development approach, the program was designed to integrate abundant local spice potential as raw materials for processing. The objectives are to enhance the technical and managerial capacity of the "Salam Makmur" farmer group in processing chicken meat into high-value products. The methods employed include hands-on training, six months of sustained mentoring, and market testing facilitation, with data collected through FGDs, pre-test/post-test questionnaires, observation, and group financial records. The results indicate a significant improvement in participants' knowledge and skills (p=0.000), with an average score increase of 48.1 points. The group successfully produced and marketed three variants of spice-based processed products (turmeric chicken dinsum, ginger-galangal chicken jerky, and chicken sticks). Economic analysis revealed an increase in added value of over 250% per chicken, with profit margins for processed products reaching 23% compared to 8-10% from live chicken sales. This program has effectively transformed the group's paradigm from raw material producers to independent micro-entrepreneurs in food processing, while also building synergy between the livestock and local spice agriculture sub-sectors. This success demonstrates that a holistic, locally-potential-based mentoring model is an effective strategy for optimizing the productivity and economic resilience of rural poultry businesses